Primary observables for indirect searches at colliders - Spencer Chang; Miranda Chen; Da Liu; Markus A. Luty (Journal of High Energy Physics, 2023)
Abstract We consider the complete set of observables for collider searches for indirect effects of new heavy physics. They consist of SU(3)C × U(1)EM invariant interaction terms/operators that parameterize deviations from the Standard Model. We show that, under very general assumptions, the leading deviations from the Standard Model are given by a finite number of ‘primary’ operators, with the remaining operators given by ‘Mandelstam descendants’ whose effects are suppressed by powers of Mandelstam variables divided by the mass scale M of the heavy physics. We explicitly determine all 3 and 4-point primary operators relevant for Higgs signals at colliders by using the correspondence between on-shell amplitudes and independent operators. We give a detailed discussion of the methods used to obtain this result, including a new analytical method for determining the independent operators. The results are checked using the Hilbert series that counts independent operators. We also give a rough sketch of the phenomenology, including unitarity bounds on the interaction strengths and rough estimates of their importance for Higgs decays at the HL-LHC. These results motivate further exploration of Higgs decays to Z f ¯ f $$ Z\overline{f}f $$ , W f ¯ f ′ $$ W\overline{f}{f}^{′ } $$ , γ f ¯ f $$ γ \overline{f}f $$ , and Zγγ.